Sub-National Performance Incentives in the Intergovernmental Framework : Current Practice and Options for Reform in Indonesia - Lewis, Blane D. (World Bank, Washington, DC, 2017)
This paper provides background for the Government of Indonesia as it considers if and how to introduce more robust local government performance incentives into the intergovernmental fiscal framework. The next section briefly examines the forces that have driven the recent national wave of interest in improving local government performance. This is followed by a review of the relatively limited set of local government performance incentives currently in force in Indonesia. The fourth section provides a conceptual overview of how to think about the possible expansion of local government incentive programs, outlining the potential role(s) of such programs in general and the key issues involved in designing and implementing them. The fifth section tentatively considers a number of options for additional local government incentives in Indonesia that the central government may wish to consider pursuing. The paper concludes with an outline of next steps for moving forward with the possible development of more purposeful and meaningful performance incentives in Indonesia's intergovernmental fiscal framework.